2013
DOI: 10.1111/jth.12106
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post-thrombotic syndrome in a population with a first deep vein thrombosis and no primary venous insufficiency

Abstract: Summary. Background: Post-thrombotic syndrome (PTS) is the most frequent complication of deep vein thrombosis (DVT). Its diagnosis is based on clinical characteristics. However, symptoms and signs of PTS are non-specific, and could result from concomitant primary venous insufficiency (PVI) rather than DVT. This could bias evaluation of PTS. Methods: Using data from the REVERSE multicenter study, we assessed risk factors for PTS in patients with a first unprovoked unilateral proximal DVT 5-7 months earlier who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 24 publications
(37 reference statements)
6
101
4
3
Order By: Relevance
“…27,44 A potential shortcoming of the Villalta scale (which also applies to other scales discussed below) is its relative nonspecificity; symptoms and signs could be due, at least in part, to nonvenous conditions or primary venous insufficiency. 45 In addition, although the presence of ulcer is noted, ulcer size and number are not. Nonetheless, the Villalta scale has been widely and successfully used to diagnose PTS, 21,35,46,47 to classify its severity, and to evaluate treatment, [48][49][50] including in randomized, controlled trials (RCTs).…”
Section: Villalta Scalementioning
confidence: 99%
See 2 more Smart Citations
“…27,44 A potential shortcoming of the Villalta scale (which also applies to other scales discussed below) is its relative nonspecificity; symptoms and signs could be due, at least in part, to nonvenous conditions or primary venous insufficiency. 45 In addition, although the presence of ulcer is noted, ulcer size and number are not. Nonetheless, the Villalta scale has been widely and successfully used to diagnose PTS, 21,35,46,47 to classify its severity, and to evaluate treatment, [48][49][50] including in randomized, controlled trials (RCTs).…”
Section: Villalta Scalementioning
confidence: 99%
“…8,10,[45][46][47]63 Older age also increases the risk of PTS. 8,11,46,47 There is no consistent association between sex and PTS; an almost equal number of studies have shown men or women to be at higher risk for PTS.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of DVT resolution was associated with PTS in children with LE-DVT in 1 previously reported pediatric study, and residual thrombosis is a known predictor of LE-PTS in adult patients. 15,[23][24][25][26] In addition, we found an interaction between sex and DVT trigger: (1) male sex was associated with a higher risk of PTS as compared with the female sex in the LR group, but this was not the case in the Non-LR group; and (2) Non-LR DVT were associated with a larger increase in risk of PTS as compared with LR-DVT among females, but this was not the case among males. The research on the association between sex and PTS in adult patients has yielded inconsistent results, and remains unclear.…”
Section: Org Frommentioning
confidence: 69%
“…c Secondary outcomes: LE-DVT resolution, recurrent LE-DVT, PE, and LE-DVT-related death were the secondary outcomes of the study. LE-DVT resolution referred to the radiologic resolution documented at the end of therapy, and was classified as complete, partial (wall thickening or worse), 15 no resolution, or extension. 16 For patients undergoing thrombolysis, "end of therapy" referred to the time immediately after this procedure (ie, end of thrombolysis).…”
Section: Introductionmentioning
confidence: 99%